Kreativitas generasi Z menggunakan bahasa prokem dalam berkomunikasi pada aplikasi TikTok - Fahra Auliani Rahmah; Ismatul Khasanah (Universitas Mulawarman, 2023)
Slang is a language that is developing among teenagers, which will threaten Indonesian authenticity because it is often used in everyday life. This study aims to analyze the formation process, characteristics, and meaning of the slang language Gen Z often uses to communicate on the TikTok application. The results of this study can be used as a reference for understanding language across generations so there are no misunderstandings in communication. Apart from that, it is also a medium for maintaining the authenticity of the Indonesian language. This study uses a qualitative descriptive method, and the data is described in the form of a narrative. The data collection process was carried out using literature review techniques. The data collected is in the form of slang found through short TikTok videos using the observing and note-taking technique. After the data has been collected, data categorization, analysis, and results are explained. The results found that the slang language that Gen Z often uses is in the form of (1) 24 data of patterned abbreviations, (2) 30 data of non-patterned abbreviations, (3) 8 data of patterned acronyms, and (4) 7 data of non-patterned acronyms.